Supporting of repairs processes of concrete industrial floors. Issue 1 (2nd January 2016) - Gajzler, Marcin
Abstract: In the large-scale facilities, including on-site storage or shopping malls, floor plays an important role. It has to meet special requirements regarding mechanical properties, aesthetics and durability. Despite much effort, both in the design and execution phase, cases of damage of the floor happens, causing some specific consequences – often associated with restrictions on use. In such a situation it is required to perform rapid diagnosis and effective repair. One possibility foster this process is the use of advisory system which operates in terms of material and technological solutions. The article points out the limitations resulting from the use of advisory system related to situations of individual and unique damage. In the case of such damage it is necessary to implement research procedures and the use of advisory system turns out to be ineffective.